PENGARUH RISIKO KREDIT, PENYALURAN KREDIT, BIAYA OPERASIONAL PENDAPATAN OPERASIONAL DAN QUICK RATIO TERHADAP PENGEMBALIAN AKTIVA DI BANK KONVESIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2016 - Suwandi, Suwandi; Loriana, Silvia; Sitorus, Friska Darnawaty; Stephanus, Andhy (Jurnal Akrab Juara, 2019)
The research objective was to test and test the effect of Credit Risk, Credit Distribution, Operational Costs of Operating Income and Quick Ratio on Returns of Assets in Conventional Banks listed on the Indonesia Stock Exchange for the 2012-2016 Period. Quantitative research approach. Types of explanatory research research. The nature of this study is a causal relationship. The population of this research is 43 Banking Companies Registered on the Indonesia Stock Exchange for the 2012-2016 period. The research sample was 25 companies. The data collection technique is documentation. The results of this study are that credit risk has an effect and is not significant on the return of assets in conventional banks listed on the Indonesia Stock Exchange for the 2012-2016 period.